A combined 2-D and 3-D QSAR modeling, molecular docking study, design, and pharmacokinetic profiling of some arylimidamide-azole hybrids as superior L. donovani inhibitors - Ugbe, Fabian Audu (2023)
Theoretical modeling of thirty-six arylimidamide-azole derivatives was conducted to establish a quantitative relationship between their structures and their inhibitory activities. As a result, a five-descriptor QSAR model was built (Eq. 13) with the descriptors well described in Table 4. The outcome of the internal and external validation assessment conducted on the built model is available in Table 5. The computed descriptors, observed activities (pIC50), and the predicted activities together with their residuals are presented in Table 6. Also, a plot of predicted activities versus experimental activities for the training set and test set is shown in Fig. 1, while Fig. 2 shows the plot of standardized residuals against experimental activities (pIC50).